Real-time Voice-over Translation - Jagdish W. Bakal; Anushka Salunke; Punnyai Suryawanshi; Neha Upadhye (International Journal of Computer Science Languages, 2024)
The real-time voice-over translation project stands as a pioneering endeavor poised to reshape the landscape of cross-cultural communication. In response to the escalating demand for fluid interaction amidst linguistic diversity, this initiative sets out to engineer a transformative solution. Its core objective lies in the seamless mediation of language barriers during real-time exchanges. Through the fusion of cutting-edge speech recognition and machine translation technologies, the project endeavors to fabricate a dynamic platform. This platform will possess the remarkable capability to instantaneously transmute spoken utterances into translated textual counterparts. By harnessing the power of sophisticated algorithms, it aims to capture, interpret, and swiftly convert diverse languages into comprehensible text. Subsequently, employing state-of-the-art text-to-speech synthesis, the translated text will be elegantly vocalized, restoring linguistic harmony in the user's preferred language. The real-time voice-over translation project harbors immense potential to redefine the boundaries of global interaction, fostering fluid dialogue across linguistic frontiers. Its envisioned impact extends beyond mere convenience, empowering individuals and enterprises alike to engage effortlessly and authentically across linguistic divides. As it navigates the forefront of technological innovation, this project embodies a beacon of inclusivity, heralding a future where language ceases to be a barrier but becomes a bridge to shared understanding and collaboration.
Keywords: Real-time voice-over Translation Project; language barriers; machine translation; real-time communication; speech recognition